Analysis of Motivating Factors of Students Desire to Become Entrepreneurs in Pekanbaru, Riau - Endrianto Ustha (Lembaga Riset dan Inovasi Al-Matani, 2023)
The purpose of this study was to analyze the effect of success themselves, would risk tolerance, freedom of work, need for achievement, and the readiness of the instrumentation in Soweto against the student wishes to become entrepreneurial. Types of data used is primary data. Methods the research was survey with inductive analysis approach to look at ways that are generally used in a tested factors influencing students ' desire to become entrepreneurs. Method of data collection using the questionnaire with the number of respondents as many as 100 people. Sampling techniques used are simple random techniques (Random Sampling Method). The data is processed and analyzed by using SPSS application assistance. Analytical tools used in this study is testing the validity, reliability, and multiple linear regression. The results of this study indicate that the variable Self Success, freedom of work and the need for achievement is dominant in the variables affect the desire of the Students in Soweto to become Entrepreneurs.